2020
DOI: 10.1126/sciadv.abd9443
|View full text |Cite
|
Sign up to set email alerts
|

Standalone or combinatorial phenylbutyrate therapy shows excellent antiviral activity and mimics CREB3 silencing

Abstract: Herpesviruses are ubiquitous human pathogens that tightly regulate many cellular pathways including the unfolded protein response to endoplasmic reticulum (ER) stress. Pharmacological modulation of this pathway results in the inhibition of viral replication. In this study, we tested 4-phenylbutyrate (PBA), a chemical chaperone–based potent alleviator of ER stress, for its effects on herpes simplex virus (HSV) type 1 infection. Through in vitro studies, we observed that application of PBA to HSV-infected cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Choice of Salubrinal does not undermine the therapeutic potential of Phenylbutyrate, a histone deacetylase inhibitor, approved for the treatment of urea cycle disorders, cancer, hemoglobinopathies, motor neuron diseases, and cystic fibrosis clinical trials (50). It possesses a broad spectrum of molecular functions such as antiviral (51), chromatin regulator and modulator of multiple cell cycle, and apoptosis-related genes (50). Phenylbutyrate has been well studied for its potential in prostate cancer alone (52) or in a combination of Phenylbutyrate and 13-cis retinoic acid (53).…”
Section: Discussionmentioning
confidence: 99%
“…Choice of Salubrinal does not undermine the therapeutic potential of Phenylbutyrate, a histone deacetylase inhibitor, approved for the treatment of urea cycle disorders, cancer, hemoglobinopathies, motor neuron diseases, and cystic fibrosis clinical trials (50). It possesses a broad spectrum of molecular functions such as antiviral (51), chromatin regulator and modulator of multiple cell cycle, and apoptosis-related genes (50). Phenylbutyrate has been well studied for its potential in prostate cancer alone (52) or in a combination of Phenylbutyrate and 13-cis retinoic acid (53).…”
Section: Discussionmentioning
confidence: 99%
“…New drug discoveries that target new viral or host molecules offer hope. These include an HSV-1 gD-targeting aptamer ( Yadavalli et al, 2017 ); innovative use of tranylcypromine to inhibit lysine-specific demethylase 1 (LSD1) which suppresses HSV-1 lytic infection, shedding, and reactivation from latency in animal models ( Hill et al, 2014 ); BX795, which inhibits AKT phosphorylation to block HSV-1 protein synthesis in corneal cells ( Jaishankar et al, 2018 ) and 4-phenylbutyrate (PBA), which reduces ER stress and synergistically increases the efficacy of existing antivirals and by its own, reduces ocular HSV-1 infection ( Yadavalli et al, 2020 ). A couple of above-mentioned drugs such as tranylcypromine and PBA are already approved for other clinical indications, therefore, their approval for treating HSV-1 infection of the eye might be more predictable timewise than the other experimental drugs.…”
Section: Current and Future Therapies To Control Ocular Herpesmentioning
confidence: 99%
“…PBA is drug used for urea cycle disorders and its effects on microorganisms are poorly studied [42]. However, some assays have shown that it can reduce Shigella infection in vivo using animal models [43], reduce colonization by Salmonella enterica serovar Typhimurium [44], inhibit the growth of Helicobacter pylori and Escherichia coli [45] and reduce herpes simplex virus infection [46]; among others. One of their advantages is also their solubility in water, thus overcome the issues generated by some antifungals that have the disadvantage of poor solubility [47].…”
Section: Effective Prevention Of C Albicans Biofilm Formationmentioning
confidence: 99%